Quality of life: actual of problem and characteristics quality of life children with bronchial asthma - Ye. L. Timoshina; S. B. Dugarova (Бюллетень сибирской медицины, 2009)
The review includes data and some results of studying the quality of life for patients with bronchial asthma from domestic and foreign literature.